Integrated zonal rotary-stirring and diameter-expansion efficiency-enhancement anchoring method and its application for large-diameter cable bolts - Ping ZHAN; Housheng JIA (Meikuang Anquan, 2025)
With the increasing depth of coal mining, soft roadways is easy to experience significant deformation of surrounding rock under the influence of mining-induced stress, leading to frequent failure of roadway support anchoring systems. Taking the transport roadway of 1302 working face of 3# coal seam in Sima Coal Mine as the engineering background, this study systematically analyzes the causes of failure in resin-based cable bolt anchoring systems for soft surrounding rock control. Through studying the structure of the resin-based cable bolt anchoring system, it was found that factors such as the size of the resin anchor agent packaging bag fragments, the mixing and reaction of the anchoring agent, and the compactness of the anchoring material have a significant impact on the bonding ability between the anchoring agent, cable bolt, and borehole wall. Bonding failure is identified as a key factor leading to the failure of resin-based cable bolt anchoring systems. To effectively rupture the resin anchor agent packaging bag, improve the mixing quality of the resin anchoring agent, and enhance the compactness of the anchoring drug body, a segmented rotary stirring-expansion integrated anchoring enhancement method is proposed, using ϕ21.6 mm large-diameter cable bolts as the research object, and an easy-to-install anchoring enhancement structure was developed to effectively enhance the anchoring effect of the resin-based cable bolt anchoring system. Through a comprehensive research approach combining laboratory tests and field tests, the effectiveness of this enhancement method in improving the quality of the anchoring system was systematically validated. Laboratory test results show that under the enhancement effect of the proposed method, the resin anchor agent packaging bag is cut into small fragments, enabling thorough mixing and reaction of the resin grout and hardener, and the compactness of the anchoring drug body is improved, and the anchoring quality of the resin cable anchoring system is greatly improved. Field test results demonstrate that when this enhancement method is applied during cable bolt installation, anchoring failure is significantly reduced, and the deformation of surrounding rock in soft roadways is effectively controlled.